IMPLEMENTASI PERMAINAN ULAR TANGGA DALAM MELATIH KEMAMPUAN MENGHAFALAN MATERI AGAMA UNTUK ANAK USIA DINI DI TPQ NURUL ISLAM DESA KEPATIHAN TIRTOYUDO-MALANG - Fitri Handayani, Ucik; Oktaviana Putri, Anggita (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2022)
Islamic religious of education plays an important role in children's lives from an early age. However, in reality there are some children who have not memorized short letters and have not understood the religious materials that have been studied. This study aims to train children to read and memorize letters and religious material through the game of snakes and ladders so that they can be practiced in daily life and to foster children's learning motivation in memorizing letters and religious materials that have been studied. The research was carried out on 25 children at the TPQ Nurul Islam in Kepatihan Tirtoyudo Village. Qualitative research method (cassus study) Data collection is done through observation and interviews. The results showed that the game of snakes and ladders can train and motivate children in learning religion and memorizing short letters in a more fun way. In addition, the application of the snake and ladder game method is followed by PAUD age children enthusiastically and happily